Correlation between the Symptoms of Depression and Sexual Function in Breast Cancer Patients Receiving Chemotherapy - Rohmawati, Dwi; Siswanto, Agus; Kurnianda, Johan; Sofia, Noor Asyiqah (Acta Interna The Journal of Internal Medicine, 2012)
ABSTRACT             Symptoms of depression and sexual problems that occur among breast cancer patients are a rarely detected and get good handling. Therefore, an early detection for any psychological problems that may affect the sexual life of patients with breast cancer is needed so that the patients can have better life. This study aims to assess the correlation between symptoms of depression and sexual function in women with breast cancer who undergo chemotherapy at Dr. Sardjito Hospital.            Research design was cross sectional. The study necquited 38 breast cancer patients in Tulip outpatients Cancer Clinic in Dr. Sardjito Hospital. Assessment of depressive symptoms used Beck Depression Inventory questionnaire and Female Sexual Function Index to assess sexual function.            The results showed that the proportion of subjects aged 46-55 years at 55.2% followed by 36-45 years of age at 39.5% and aged 26-35 years by 5.3%. The mean age of subjects was 45.4 + 6.5 years. Correlation between symptoms of depression with sexual function among participants was r=- 0.30 with significance p=0.068. Correlation between symptoms of depression with the domains of sexual function domain of desire (r=-0.296, p=0.072), stimulation (r = -0.470, p = 0.003), lubrication (r=-0.353, p=0.030), orgasm (r=-0.223, p=0.179), satisfaction (r=-0.233, p=0.158), pain (r=-0.186, p=0.262).            The conclusion is that there is no correlation between symptoms of depression with sexual function. Keywords: Depression symptoms, Breast Cancer, Sexual Dysfunction